The virtual patient as a learning tool: A mixed quantitative qualitative study (2018)
Background: The use of simulation in medical education has been widely accepted. There are different types of medical simulators that vary in both accuracy to emulate the real world (fidelity) and cost of development or acquisition. There is significant evidence that supports the use of high-fidelity simulators (i.e. mannequins or dummies) to prepare students for clinical environments, less attention has been given to low-fidelity simulators. This article aims to present evidence regarding the effectiveness of a low-fidelity simulator: Virtual Patient (VP), which develops several interactive computer-based clinical scenarios, seeking to promote an alternative learning environment and the development of necessary medical skills such as clinical reasoning in students of medicine. Methods: A quasi-experimental study was designed to investigate the results on the development of history taking and clinical reasoning skills in a group of undergraduate medical students, in a course devised under the concepts of constructivism in education, which used the Virtual Patient as the fundamental teaching tool. Results were measured through a mixed, quantitative and qualitative study, triangulating the results of the students' skills evaluation when facing a clinical case represented by an actor patient before and after the course. Additionally, the description of the students' and tool's performance was measured by way of a qualitative study. Results: The comparison of the students' skills on the evaluation matrix before-and-after the course evidenced a statistically significant advance (p less than 0.01) in all aspects (interview, physical exam, clinical judgment, relevance of medical exams, and presentation of case). Students described the VP as an easy-to-use and motivating tool for learning without stress, especially at the beginning of their career. VP allowed them to create logical and structured processes, to be wrong without consequences, and to review and reassess information available. From the professor perspective, it allowed a better follow-up of the students' learning process and favored reflections on the teaching-learning process. Conclusions: VP proved to be a valuable and useful tool for the development of clinical reasoning and history taking skills in medical students, as part of a constructivist learning course. © 2018 The Author(s).